Енергоємність валового внутрішнього продукту України: сутність, тенденції, перспективи - Lyashenko O.F. (General Energy Institute of the National Academy of Sciences of Ukraine, 2002)
The dynamic of the of energy output IMP of Ukraine for period 1990-2001 years has been done. The factors conditioning forming of the determined tendencies of variation of energy output IMP are determined and rated. The essence of an index of energy output IMP is described and the boundaries their correct usages are determined. The premises of drop of energy output IHP in the long-term period are determined.